588 THE INFLUENCE OF CHANGE OF DIET COMPOSITION ON ESOPHAGEAL MOTILITY PATTERNS IN PATIENTS WITH NON-EROSIVE GERD. (14th September 2020) - Morozov, S; Isakov, V
Abstract: : The aim of the study was to evaluate the influence of change in diet composition on high-resolution esophageal manometry (HRM) patterns. Methods: The data of 43 NERD patients with low (<20 g/day) dietary fibre intake served as a source data. These patients were examined with the use of standard food frequency questionnaire and HRM. Thirty of them received psyllium 5.0 G TID 10 days additionally to their usual diet (NCT01882088). Control group was formed by the database search for patients who had repeated HRM examinations and dietary assessments at the same time point and if no significant change in diet composition was revealed. HRM assessment was in accordance to Chicago-3.0. Non-parametric statistics were used to assess the change in HRM metrics. Results: Minimal LES resting pressure at rest and after 10 water swallows increased in study group: 5.41 ± 10.1 vs 11.3 ± 9.4 mmHg, P = 0.023 and 14.1 ± 8.0 vs 14.9 ± 6.4 mmHg, P = 0.008. No difference was found in those whose diet composition was stable. Ineffective esophageal motility initially was found in 46.7% patients of the study group and 53.8% in the control group (P = 0.7). IEM resolved in 71.4% of the study group, and in 14.3% of controls (P = 0.0135). IEM not changed in 28.6% of the study group and in 85.7% of controls, P = 0.014. New IEM revealed in 12.5% of the study group and 16.7% among the controls (P = 0.13). Conclusion: Change of diet composition by additional quantity of dietary fibre (psyllium) to the standard rations may result in the improvement of esophageal motility.